Longitudinal changes in LIC and other parameters in patients receiving different chelation regimens: Data from LICNET. (7th December 2017) - Vitrano, Angela; Sacco, Massimiliano; Rosso, Rosamaria; Quota, Alessandra; Fiorino, Daniela; Oliva, Esther; Gerardi, Calogera; Roccamo, Gaetano; Spadola, Vincenzo; Filosa, Aldo; Tesé, Lorenzo; Calvaruso, Giuseppina; et al.
Abstract: Objectives: The liver remains the primary site of iron storage, with liver iron concentration (LIC) being a strong surrogate of total body iron. MRI‐R2 can accurately measure LIC. The LICNET (Liver Iron Cutino Network) was established to diagnostics of liver iron overload by MRI‐R2 subjects with hemochromatosis in hematological disorders. The aims of the study were to look at variation in LIC measurements during time across different chelation regimens. Methods: This was a cross‐sectional study of 130 patients attending 9 Italian centers participating in the LICNET. LIC comparisons over time (T0 and T1 ) were made using t test and/or Wilcoxon test. Results: LIC significantly decreased from MRI1 to MRI2 although at high variance (median change −0.8 mg Fe/g dw, range: −29.0 to 33.0; P  = .011) and 7.7% of patients shifted from LIC values of high risk (>15 mg Fe/g dw) to an intermediate‐risk category (7‐15 mg Fe/g dw). Median change in LIC and correlation with serum ferritin levels (SF), during different chelation regimens, is reported. Conclusions: These findings suggest as longitudinal variation in the LIC is possible, across all chelation regimens. It confirms as SF levels not always can be used for estimating changes in LIC.